In Vitro Testing of Alternative Synthetic and Natural Antiparasitic Compounds against the Monogenean Sparicotyle chrysophrii - Mladineo, Ivona; Trumbić, Željka; Ormad-García, Adrián; Palenzuela, Oswaldo; Sitjà-Bobadilla, Ariadna; Manuguerra, Simona; Ruiz, Cristobal Espinosa; Messina, Concetta Maria (Pathogens, 2021)
Gill monogenean Sparicotyle chrysophrii is considered the most detrimental fish parasite to the Mediterranean aquaculture. Treatment of sparicotylosis relies on frequent gill inspections correlated with the seasonal increase in seawater temperature, application of functional feeds, and treatments with formalin baths where permitted. While the latter is bound to be banned in Europe, other synthetic anthelminthics, such as praziquantel and ivermectin, are prone to induce resistance in the parasites. Therefore, we investigated, in vitro, 14 synthetic and natural compounds against adult S. chrysophrii, developing dose-response modelsm and estimated toxicity levels at 20%, 50%, and 80% parasite mortality. Bactericidal activity of target compounds was also tested in two important aquaculture bacteria; Vibrio harveyi and V. anguillarum, while their potential host toxicity was evaluated in gilthead seabream SAF-1 cell line. Synthetic compound bithionate sodium exerted the most potent toxicity against the monogenean, no host cytotoxicity, and a medium and high potency against two bacterial pathogens. In comparison, target natural compounds were approximately 20 (cedrol) or up to 154 times (camphor) less toxic for the monogenean. Rather than completely dismissing natural compounds, we suggest that their application in combination with synthetic drugs, especially if administered in the feed, might be useful in sparicotylosis treatment.